2019
DOI: 10.1074/jbc.ra119.007709
|View full text |Cite
|
Sign up to set email alerts
|

Structure and interactions of the archaeal motility repression module ArnA–ArnB that modulates archaellum gene expression in Sulfolobus acidocaldarius

Abstract: Phosphorylation-dependent interactions play crucial regulatory roles in all domains of life. Forkhead-associated (FHA) and von Willebrand type A (vWA) domains are involved in several phosphorylation-dependent processes of multiprotein complex assemblies. Although well-studied in eukaryotes and bacteria, the structural and functional contexts of these domains are not yet understood in Archaea. Here, we report the structural base for such an interacting pair of FHA and vWA domain-containing proteins, ArnA and Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…cells (Hoffmann et al, 2019). The C-terminal domain of ArnB could be phosphorylated by ArnC in vitro (Hoffmann et al, 2017) and was found phosphorylated in vivo, which suggested that phosphorylation/dephosphorylation of this domain might influence its interaction with ArnA (Hoffmann et al, 2019).…”
Section: Identification Of Proteins Associated With Ptp and Pp2amentioning
confidence: 99%
See 3 more Smart Citations
“…cells (Hoffmann et al, 2019). The C-terminal domain of ArnB could be phosphorylated by ArnC in vitro (Hoffmann et al, 2017) and was found phosphorylated in vivo, which suggested that phosphorylation/dephosphorylation of this domain might influence its interaction with ArnA (Hoffmann et al, 2019).…”
Section: Identification Of Proteins Associated With Ptp and Pp2amentioning
confidence: 99%
“…Deletion of arnR and arnR1 reduced flaB expression and impaired swimming motility. Previous experiments showed that ArnR and ArnR1 regulated the flaB promoter, but not the flaX promoter (Lassak et al, 2013;Bischof et al, 2019). AbfR1, an archaeal biofilm regulator, is also a positive regulator for archaellum expression and its binding to DNA is phosphorylation dependent (Orell et al, 2013;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In bacteria, FHA-containing proteins were able to bind phosphorylated proteins ( Alderwick et al, 2006 ; Niebisch et al, 2006 ). In S. acidocaldarius , the interaction of FHA and vWA1 was mediated by phosphorylation and the cell motility was regulated by this interaction ( Reimann et al, 2012 ; Albers and Jarrell, 2015 ; Hoffmann et al, 2019 ; Ye et al, 2020 ). Our data suggested that vWA2 might also be phosphorylated and interacted with FHA in vivo .…”
Section: Resultsmentioning
confidence: 99%